Anteseden Pengelolaan Keuangan Desa : (Studi Empiris pada Desa Se-Kecamatan Trawas Kabupaten Mojokerto) - Debora Freti Gracia; Loggar Bhilawa (Pusat Riset dan Inovasi Nasional, 2024)
The public has the right to know information, transparency and accountability of regional financial management so that the presentation of financial reports can be accessed by various parties. Therefore, the purpose of this study was to determine whether transparency, accountability, community participation and the role of village officials have a positive effect on village financial management. The method used in this research is a quantitative method whose data comes from primary data in the form of questionnaires. The sample in this study were 380 people in Trawas District. The sampling technique used in this study used purposive sampling technique. The independent variables in this study are transparency (X1), accountability (X2), community participation (X3), and the role of village officials (X4). The dependent variable in this study is village financial management (Y). The data analysis that the authors use in this quantitative research uses statistics using IBM SPSS software version 25 The results of this study are the village financial management of Trawas Regency is positively and significantly influenced by transparency, accountability, community participation, and the role of village officials.